2013
DOI: 10.1002/adma.201300342
|View full text |Cite
|
Sign up to set email alerts
|

Use of Magnetic Forces to Promote Stem Cell Aggregation During Differentiation, and Cartilage Tissue Modeling

Abstract: Magnetic forces induce cell condensation necessary for stem cell differentiation into cartilage and elicit the formation of a tissue-like structure: Magnetically driven fusion of aggregates assembled by micromagnets results in the formation of a continuous tissue layer containing abundant cartilage matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 47 publications
2
96
0
5
Order By: Relevance
“…Of importance, the magnetization is also found to be capable of further promoting this effect, which hints that the magnetic effect should play a crucial role. Many studies have reported that the magnetic nanoparticles can promote the differentiation of marrow-derived stem cells toward osteoblasts [25][26][27]. We also utilized the Au nanoparticles to do the same experiments, but it was found that the LBL-assembled colloidal Au film was unbeneficial for the differentiation of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Of importance, the magnetization is also found to be capable of further promoting this effect, which hints that the magnetic effect should play a crucial role. Many studies have reported that the magnetic nanoparticles can promote the differentiation of marrow-derived stem cells toward osteoblasts [25][26][27]. We also utilized the Au nanoparticles to do the same experiments, but it was found that the LBL-assembled colloidal Au film was unbeneficial for the differentiation of cells.…”
Section: Resultsmentioning
confidence: 99%
“…magnetoelasticity | buckling | nanoparticles | instability | magnetic I n the past decade there has been an emerging field of research on new magnetic and elastic soft materials whose shape can be remotely controlled by application of an external magnetic field (1)(2)(3). Indeed, at many scales and in various domains, magnetic filaments (4,5), gels (6), and so on (7) show great promise in numerous domains of application (8). With the progress in the design of these materials, their magnetic susceptibility increases, and brings them closer to the behavior of the more conventional magnetic alloys.…”
mentioning
confidence: 99%
“…The first step of magnetic cell manipulation is to magnetically label cells by coculturing them with ferromagnetic particles. Then, by applying an external magnetic field, these magnetically tagged cells would organize to form defined cell patterns with certain sizes and shapes . For example, magnetically labeled human mesenchymal stem cells were observed to aggregate into rod‐like tissues or sheet‐like tissues under the impact of magnetic tips or magnetic sheets, respectively.…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%